Stent-based electrode for radiofrequency ablation in the rat esophagus: a preliminary study - Dong-Sung Won; Yubeen Park; Jinsu An; Dae Sung Ryu; Jeon Min Kang; Ji Won Kim; Song Hee Kim; Chu Hui Zeng; Hongbae Kim; Hyung-Sik Kim; Jung-Hoon Park; Sang Soo Lee (Scientific Reports, 2022)
Abstract Endoluminal radiofrequency (RF) ablation has been widely used as a safe and effective treatment for Barrett’s esophagus. However, inadequate RF ablation may occur due to insufficient contact between the electrode and target tissues. Herein, a stent-based monopolar RF electrode (SE) was developed to evenly deliver RF energy to the inner wall of the rat esophagus. The optimal RF parameters were evaluated in the exposed rat esophagus. The temperature in the rat esophagus reached 70 ℃ in 89 s at 30 W, 59 s at 40 W, and 34 s at 50 W. The technical feasibility and efficacy of RF ablation using SE were evaluated based on changes in histological transformation and immunohistochemical parameters of tissues compared at immediately, 1 and 2 weeks after the procedure. The degrees of inflammatory cell infiltration, fibrotic changes, TUNEL, and HSP70 in the RF-ablated rat esophagus were significantly higher than compared with sham control (all p < 0.05). TUNEL-positive deposition gradually decreased, but HSP 70-positive deposition maintained a similar level for 2 weeks. The stent-based RF ablation was technically feasible and effective in evenly inducing thermal damages to the rat esophagus. The RF ablation system using the SE may represent a promising treatment for endoluminal malignancies.